Analisis Keadilan Substantif Dalam Putusan Pengadilan Mengenai Kasus Penipuan Melalui Media Sosial - jeshlyn, jeshlyn; Fitri, Winda; Tantimin, Tantimin (Prodi Ilmu Hukum, Universitas Teuku Umar, 2025)
This article examines the application of substantive justice in court decisions related to social media fraud, focusing on Court Decision Number 63/Pid.Sus/2022/PN Btm. The rapid expansion of digital platforms, such as WhatsApp and Facebook, has led to a substantial rise in technology-based fraud cases, presenting significant new challenges for consumer protection in the digital era. In Indonesia, social media fraud falls under the Consumer Protection Law (UUPK) and the Electronic Information and Transactions Law (UU ITE), which provide general legal grounds but lack specific provisions to address the complexities of fraud on social media platforms. As a result, legal gaps arise, requiring judges to interpret laws in cases where existing regulations are limited or ambiguous. Using a normative juridical approach and case study analysis, this research highlights that applying substantive justice necessitates judicial consideration of both legal aspects and the social and emotional harm experienced by victims. The court ruling analyzed emphasizes the need for sentences that serve not only a punitive purpose but also educational and preventive functions, reinforcing public trust in digital transactions and deterring similar crimes in the future. This study underscores the importance of judicial discretion in interpreting laws to adapt to the unique challenges of social media fraud cases, including the wide-reaching impacts on victims’ lives and society. The findings point to an urgent need for updated regulatory frameworks, stronger enforcement mechanisms, and greater public awareness to protect consumers more effectively within the digital landscape, ensuring that legal protections evolve alongside rapidly advancing technology in society.